Designing Performance Measurement with the Balanced Scorecard Method in the Tourism Service Industry - Nasuka, Dody Saptadi; Hasbullah, Hasbullah (Journal of Industrial Engineering & Management Research, 2020)
The research in this paper discusses the performance measurement of a tourism service company. The performance measurement that is done is the measurement used by the company at this time and the measurement of performance using the Balanced Scorecard (BSC) method. The purpose of this research is to identify the performance measurement system that is currently being used by the company, to measure performance using the BSC method and to make improvements with the strategy map and Key Performance Indicators (KPI) tables produced by this study. The process of weighting the perspectives and main indicators of making KPI tables uses the Analytical Hierarchy Processes (AHP) method. This research shows that the measurement method used by the company is currently inadequate and the BSC method is the right measurement system needed for now and for the future. The results of measuring company performance in 2019, the biggest is financial performance with a performance score of 0,694, second place is customer performance with a performance score of 0,691, in third place is growth and learning performance with a performance score of 0,560 and the last order is the performance of internal business processes with a score performance 0,551. The company's performance score is 2,496 (with a mean of 0,624). This means that the company's current performance is still not good.